An investigation into coach developers' theories in practice, learning, and development on a continuing professional development course - Partington, M.; O`Gorman, J.; Greenough, K.; Cope, E. (International Sport Coaching Journal, 2022)
Little is known about the development of coach developers despite their importance in supporting coach learning. In response, this study explored the theories in practice of 23 English coach developers who undertook a continuing professional development course. The data were collected through semistructured interviews, focus groups, and observations of coach developers` practice and engagement on the course. The data were analysed using a phronetic-iterative approach, with Argyris and Schön`s ideas on theories in practice, mostly espoused theories and theories-in-use, providing the primary heuristic framework. The findings identified how, before the continuing professional development course, the coach developers articulated espoused theories, but as the course progressed, there was a move to theories-in-use. This was due to their (re)constructed understanding of learning and the working environment. The findings are discussed in light of how the continuing professional development course, and tutors` pedagogic approaches, influenced the coach developers` knowledge and understanding. Based on these findings, it seems there is much to gain from supporting coach developers with a deconstruction and reconstruction of theories in practice.